ACCOUNTING FOR DEBT SECURITY: PROBLEMS AND WAYS OF ITS DECISION - Karmazinа , N.V. (The actual problems of regional economy development, 2018)
The article reveals problems related to accounting of receivables consisting in the absence of a clear ratio of accounts receivable and payables in their general structure; unsuitability of methods for determining the reserve of doubtful debts, which are envisaged in P (C) BO 10, for accounting at Ukrainian enterprises; differentiation of concepts of short-term and long-term receivables, etc. The classification of receivables is systematized according to the following criteria: definition of purpose, task formulation, specification of users of information, choice of classification mark, determination of priority principles, selection and grouping of receivables by the optimal type, and additionally proposed: subject of accounts receivable, amount of arrears , type of assessment, cause of occurrence. This allowed to identify such methods for assessing debt as, historical cost; cost of realization (repayment) - factoring, forfaiting estimation, valuation at the discount of a bill; based on current value; present value. The complex methodical approach to calculating the reserve of doubtful debts is proposed, which contains analytical and mathematical model of calculation. The analytical model consists in assessing the level of solvency of the debtor on the basis of developed criteria of the insolvency level, the results of which write off the receivables buyers and reflect the written off amounts as doubtful debt. It is substantiated that the mathematical model of determining the value of the reserve, which is based on the method of classification of receivables for the terms of non-payment. Using of a comprehensive methodical approach to calculating the reserve of doubtful debts provides the development of a comprehensive policy for calculating such a reserve, based on a comprehensive assessment of the size, composition and timing of accounts receivable for products, goods, works and services, taking into account the specifics of the entity. It is argued that most of the joint-stock companies, whose reporting is compulsory, do not create a reserve of doubtful debts, for reasons such as: a). this requires the withdrawal of funds that may be involved in other areas of activity; b). enterprises do not want to incur additional labor costs to create this reserve. The prospects of ensuring efficient accounting of receivables are substantiated. The optimization form of accounting of accounts receivable, the attributive features of which include: a). the availability of a single approach to the accounting of debts (receivables and payables), which provides for the possibility of comparative analysis and general assessment of receivables and payables, as well as the association of accounting entities (any enterprise may be in the role of debtor and creditor); b) high-quality accounting of long-term receivables, which provides for the development of a single approach to the registration and accounting of long-term receivables in the system of synthetic accounts; conducting analytical accounting for each type of long-term receivables in the developed information of analytical accounting; generalization and accumulation of analytical information on long-term receivables. In these conditions, the creation of an effective accounting model for accounts receivable will help to avoid insolvency risks and decrease of liquidity indicators due to obtaining objective and timely information for making optimal managerial decisions.